The role of information technology and its impact on knowledge management process for organizational sustainability in the context of gaining a competitive advantage/ Pritam Kumar - Kumar, Pritam (Faculty of Information Management, 2021)
This study used a descriptive approach to investigate the theoretical framework of the role of information technology and its impact on knowledge management processes. The theoretical framework was developed through a review of previous research, which was carried out by the researchers. Information technology and knowledge management practises were used to select the sample organisations, which were then evaluated on their effectiveness. This study investigates the potential of organizations to influence the long-term development of their organizations by using information technology to improve knowledge availability and human resource management. According to the study's findings, information technology has a statistically significant positive relationship with the implementation and utilisation of knowledge management for the organization's long-term development. The findings of this study provide some suggestions and recommendations for improving the overall performance of the organisation. This study provides fundamental guidelines on the practical and managerial implications of the findings.